PENGARUH PARTISIPASI ANGGARAN, INFORMASI ASIMETRI, KOMPLEKSITAS TUGAS DAN PENEKANAN ANGGARAN TERHADAP SENJANGAN ANGGARAN PADA INSTANSI PEMERINTAH DAERAH (Survei Pada SKPD Pemerintah Kabupaten Bengkalis) - Yeandrawita -; Muhammad Rasuli; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to test the effect of budget participation, information asymmetry, the emphasis budget and complexity of the task on the government budgetary slack in Bengkalis. Data was colleted by distributing questionnaires to the respondents. The population used in this study are staff / staff involved in the preparation of the budget, the number of samples taken at 128 people but the samples that can processed is 104 people. The data analysis technique used in this study is the technique of multiple regression analysis by using SPSS version 20.0. These results indicate the three variables that effect budgetary slack and only one variable that does not have an influence on budgetary slack. The result of this information asymmetry, the complexity in the task and budget emphasis have significantly effect on budgetary slack. While budget partiscipation don’t have significantly effect on budgetary slack.Keywords: Budget Participation, Information Asymmetry, The Complexity of The task, Budget Emphasis, and Budgetary Slack.